2021
DOI: 10.1016/j.jcot.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

How hand and wrist trauma has changed during covid-19 emergency in Italy: Incidence and distribution of acute injuries. What to learn?

Abstract: Background: the purpose is to gather and analyze the statistical datas of wrist and hand injuries admitted to the Hand and Reconstructive Microsurgery and Replantation Hub center of Careggi Hospital, Florence during the first two months of COVID-19 epidemic in Italy. The Authors investigated how the drastic changes in daily activities modified the epidemiology of hand trauma lesions. Methods: The Authors analyzed the characteristics of hand and wrist traumatic disorders during the months of February and March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 7 publications
6
41
0
Order By: Relevance
“…A reduction in trauma occurring secondary to RTCs was reported in the UK, 10 , 20 , 45 , 49 US 17, 26, 40, 51, 52, 55 , New Zealand, 12 Australia, 31 , 50 India, 53 , 57 Iran, 37 Hong Kong 58 and Europe. 13 , 19 , 22 , 36 , 59 , 60 These reductions reached statistical significance in Jacob et al‘s Australian centre (34% v 46%, p = 0.025), and Sherman et al‘s US centre (42% v 49%, p = 0.03). An increase in injuries from RTCs in children was reported by Bram et al in the US (5.2% v 1.8%) 11 and UK by Sugand et al (2% v 1%).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…A reduction in trauma occurring secondary to RTCs was reported in the UK, 10 , 20 , 45 , 49 US 17, 26, 40, 51, 52, 55 , New Zealand, 12 Australia, 31 , 50 India, 53 , 57 Iran, 37 Hong Kong 58 and Europe. 13 , 19 , 22 , 36 , 59 , 60 These reductions reached statistical significance in Jacob et al‘s Australian centre (34% v 46%, p = 0.025), and Sherman et al‘s US centre (42% v 49%, p = 0.03). An increase in injuries from RTCs in children was reported by Bram et al in the US (5.2% v 1.8%) 11 and UK by Sugand et al (2% v 1%).…”
Section: Resultsmentioning
confidence: 86%
“…The reported proportion of patients undergoing closed reduction and open reduction and internal fixation (ORIF) and external fixation remained largely comparable before and after the pandemic in reporting centres based in Australia, 31 US, 11 Europe 59 and the UK. 10 , 54 …”
Section: Resultsmentioning
confidence: 99%
“…Distal radius fractures constitute a social problem [1][2][3][4][5][6][7][8][9][10][11][12][13]. The COVID-19 pandemic has had a considerable impact on the lives of both adults and children around the world [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Some schools have been closed, causing children to stay at home, and some adults work from home.…”
Section: Discussionmentioning
confidence: 99%
“…Hashmi reported a 50% decrease in both elective and emergency admissions to orthopedic wards, with no changes in either the mean age or male-to-female ratio in patients in the COVID-19 pandemic period in comparison with the relevant prepandemic figs [16].. Yu et al observed a 42% decrease in the number of patients with fractures seen at one of the orthopedic wards in China during the COVID-19 epidemic [17]. Poggetti et al reported a 28.6% decrease in the number of patients undergoing surgery due to hand and wrist trauma in one of Italian hospitals during the COVID-19 pandemic [18]. In one of the Turkish hospitals, the total number of fractures recorded during the COVID-19 pandemic was by 61.6% lower than the number of fractures recorded in 2019 [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation